Platelets regulate ischemia-induced revascularization and angiogenesis by secretion of growth factor-modulating factors - Nording, Henry Morten; Baron, Lasse; Sauter, Manuela; Lübken, Antje; Rawish, Elias; Szepanowski, Rebecca; von Esebeck, Jacob; Sun, Ying; Emami, Hossein; Meusel, Moritz; Saraei, Roza; Schanze, Nancy; et al. (Blood advances, 2023)
In ischemic tissue, platelets can modulate angiogenesis. The specific factors influencing this function, however, are poorly understood. Here, we characterized the complement anaphylatoxin C5a-mediated activation of C5a receptor 1 (C5aR1) expressed on platelets as a potent regulator of ischemia-driven revascularization. We assessed the relevance of the anaphylatoxin receptor C5aR1 on platelets in patients with coronary artery disease as well as those with peripheral artery disease and used genetic mouse models to characterize its significance for ischemia and growth factor-driven revascularization. The presence of C5aR1-expressing platelets was increased in the hindlimb ischemia model. Ischemia-driven angiogenesis was significantly improved in C5aR1−/− mice but not in C5−/− mice, suggesting a specific role of C5aR1. Experiments using the supernatant of C5a-stimulated platelets suggested a paracrine mechanism of angiogenesis inhibition by platelets by means of antiangiogenic CXC chemokine ligand 4 (CXCL4, PF4). Lineage-specific C5aR1 deletion verified that the secretion of CXCL4 depends on C5aR1 ligation on platelets. Using C5aR1−/−CXCL4−/− mice, we observed no additional effect in the revascularization response, underscoring a strong dependence of CXCL4 secretion on the C5a-C5aR1-axis. We identified a novel mechanism for inhibition of neovascularization via platelet C5aR1, which was mediated by the release of antiangiogenic CXCL4.
Online veröffentlicht: 25 Oktober 2023
Gesehen am 01.10.2024